NEXT-GENERATION MODULAR PIM CONCEPT FOR MULTICHANNEL ONLINE RETAIL - Svynarov, Serhii (Global Prosperity, 2024)
Abstract. Multichannel online retail has run into a problem - product information is scattered across different systems and platforms, nobody knows where the truth is. Traditional PIM systems are supposed to solve this, but their implementation takes too long, costs too much money, and creates too many risks during integrations. Plus, the company then gets locked into one vendor. This paper proposes a different approach - a modular adaptive PIM concept (Modular Adaptive PIM Framework). We implement in stages, integrate via API-first, scale in a controlled manner. First, we audit what already exists. Then we form a minimally sufficient attribute model - not everything at once, but only what is absolutely necessary at the start. We enable governance mechanisms to control product information quality. The result - implementation times are reduced, technical risks are minimized, data centralization works stably even when sales channels are constantly being added.